METAL 2020 Conference Proeedings 2020
DOI: 10.37904/metal.2020.3655
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and limitations of using the QFD method in the production of copper PRODUCTS – CASE study

Abstract: In the paper customer preferences regarding copper wires were determined, special attention to the technical characteristics of wires were focused, that would meet customer expectations. To build a quality house, information from direct production employees as well as technologists and constructors were used. The application of the QFD method allowed of rendition of consumer requirements (customer voice) into technological parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The House of Quality is a powerful tool for establishing specific target values for engineering characteristics and analysing competitive opportunities, regardless of the product type. It has found application in the design of various products, such as automotive batteries [14], a car dashboard [15], universal parts of pick-and-place machines [16], tyres [17], copper wires [18], school furniture [19], a coffee machine [20], a smartphone [21], an automatic filling machine [22], and even in defining new characteristics of confectionery products [23]. On the basis of the published case studies, it can be safely concluded that the use of this important tool has allowed researchers, engineers, and designers to identify the most critical features of the product, thus ensuring a higher level of customer satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The House of Quality is a powerful tool for establishing specific target values for engineering characteristics and analysing competitive opportunities, regardless of the product type. It has found application in the design of various products, such as automotive batteries [14], a car dashboard [15], universal parts of pick-and-place machines [16], tyres [17], copper wires [18], school furniture [19], a coffee machine [20], a smartphone [21], an automatic filling machine [22], and even in defining new characteristics of confectionery products [23]. On the basis of the published case studies, it can be safely concluded that the use of this important tool has allowed researchers, engineers, and designers to identify the most critical features of the product, thus ensuring a higher level of customer satisfaction.…”
Section: Introductionmentioning
confidence: 99%